Biological deterioration of wooden structures of the Bialystok open-air museum - Perebynos, Alona; Kryvomaz, Tetyana (My University, 2017)
The preliminary survey of the biodeterioration in the Bialystok open-air museum (Poland) shows that wooden buildings are in good condition and 92% of historical and architectural constructions were estimated to the second category of technical state. Buildings were examined to identify kinds of biological agents. The main biodeteriorations of wooden constructions were made by insects, lichens, algae films and colonies of microfungi. The comparison of the biodeterioration impact was made for the Bialystok open air museum and the skansen "Pyrogovo" (Ukraine). The probability of germination on the wooden structures of some species of fungi has been calculated taking into account the temperature conditions of the north-eastern region of Poland.
Keywords: open-air museum; wooden buildings; biological deterioration; mycological damage; музей під відкритим небом; дерев’яні будівлі; біологічне погіршення; мікологічні пошкодження